Neutrophil Gelatinase Associated Lipocalin (NGAL) for Identification of Unstable Plaques in Patients with Asymptomatic Carotid Stenosis. (June 2019) - Eilenberg, Wolf; Stojkovic, Stefan; Kaider, Alexandra; Piechota-Polanczyk, Aleksandra; Nanobachvili, Josif; Domenig, Christoph M.; Wojta, Johann; Huk, Ihor; Demyanets, Svitlana; Neumayer, Christoph
Abstract : Objective: Neutrophil gelatinase associated lipocalin (NGAL) and matrix metalloproteinase (MMP)-9/NGAL complex were investigated in asymptomatic patients with carotid artery stenosis including gender specific differences aiming at vulnerable plaques prone to embolisation. Methods: Serum NGAL and MMP-9/NGAL levels were analysed in 83 patients with asymptomatic carotid artery stenosis. Pre-operative ultrasound and post-endarterectomy histology of carotid atherosclerotic lesions were evaluated. Results: Patients with vulnerable plaques, as determined by ultrasound (plaques with decreased echogenicity) and histological analysis (type VI according to the classification of the American Heart Association), displayed the highest levels of NGAL and MMP-9/NGAL complex ( p = .0003 and p = .0078, respectively). Grade VI plaques were primarily detected in patients with "soft" plaques (12 type VI plaques in 25 patients), but also in patients with mixed (four of 19) and calcified (three of 39) plaques according to ultrasound. Higher grade carotid artery stenosis (≥90%) was not associated with elevated NGAL levels. The receiver operating characteristic curve analysis detecting grade VI lesions yields an area under the curve (AUC) = 0.85, with respect to soft plaque on ultrasound the AUC = 0.86. There were no gender specific differences in levels of NGAL 80.9 (37.7) ng/mL in women vs. 76.7 (36.3) ng/mL in men, p = .607) nor of MMP-9/NGAL 33.0 (18.2–55.5) ng/mL in women vs. 36.7 (20.2–54.0) ng/mL in men, p = .969. Likewise, there were no gender associated differences in vulnerable plaque characteristics: either for grade VI plaques (17.9% vs. 27.3%, p = .582) or for the presence of soft plaques as evaluated by ultrasound (35.9% vs. 25%, p = .503). Conclusion: Circulating NGAL and MMP-9/NGAL are significantly increased in asymptomatic patients with vulnerable carotid atherosclerotic plaques independent of gender. Accordingly, serum NGAL may be proposed as a valuable biomarker for the detection of unstable carotid plaques in asymptomatic patients, who can then be selected for early carotid endarterectomy or stenting.